2011
DOI: 10.1037/a0022738
|View full text |Cite
|
Sign up to set email alerts
|

Anomia as a marker of distinct semantic memory impairments in Alzheimer's disease and semantic dementia.

Abstract: Objective-Many neurologically-constrained models of semantic memory have been informed by two primary temporal lobe pathologies: Alzheimer's Disease (AD) and Semantic Dementia (SD). However, controversy persists regarding the nature of the semantic impairment associated with these patient populations. Some argue that AD presents as a disconnection syndrome in which linguistic impairment reflects difficulties in lexical or perceptual means of semantic access. In contrast, there is a wider consensus that SD refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 138 publications
5
57
1
7
Order By: Relevance
“…Results from a selected group of patients with primary progressive aphasia and exclusive or predominant atrophy within the left ATL revealed a substantial number of anomic errors (Mesulam et al 2013). Also supporting this result, patients with semantic dementia, principally associated with atrophy in anterolateral and ventral cortex, were found to make more omissions than patients with Alzheimer's disease, primarily associated with damage to MTL (Reilly et al 2011). Additionally, when we evaluated the effects of relevant psycholinguistic factors on object naming, we found that all participants showed an influence of age of acquisition and concept familiarity (Graves et al 2007;Hirsch and Funnell 1995;Lambon Ralph et al 1998;Rogers et al 2004).…”
Section: Discussionmentioning
confidence: 65%
“…Results from a selected group of patients with primary progressive aphasia and exclusive or predominant atrophy within the left ATL revealed a substantial number of anomic errors (Mesulam et al 2013). Also supporting this result, patients with semantic dementia, principally associated with atrophy in anterolateral and ventral cortex, were found to make more omissions than patients with Alzheimer's disease, primarily associated with damage to MTL (Reilly et al 2011). Additionally, when we evaluated the effects of relevant psycholinguistic factors on object naming, we found that all participants showed an influence of age of acquisition and concept familiarity (Graves et al 2007;Hirsch and Funnell 1995;Lambon Ralph et al 1998;Rogers et al 2004).…”
Section: Discussionmentioning
confidence: 65%
“…Underlying impairments of conceptual knowledge have been demonstrated with non-linguistic semantic tasks such as semantic matching between pictures (Bozeat, Lambon Ralph, Patterson, Garrard, & Hodges, 2000), object use (Hodges, Bozeat, Lambon Ralph, Patterson, & Spatt, 2000), sound to picture matching (Bozeat et al, 2000), picture categorization (Rogers & Patterson, 2007), knowledge of object features (Adlam et al, 2006; Rogers et al, 2004) and delayed picture copy (Patterson & Erzinçlioğlu, 2009); see Hodges and Patterson (2007) for review. Furthermore, the progression and severity of naming deficits are strongly associated with the progression and severity of the deterioration of conceptual knowledge (Adlam et al, 2006; Hodges et al, 1995; Jefferies & Lambon Ralph, 2006; Lambon Ralph, McClelland, Patterson, Galton, & Hodges, 2001; Rogers et al, 2004; Reilly, Peelle, Antonucci, & Grossman, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…word retrieval, working memory and language). Examples of tests with semantic content are naming of objects [7,8] as well as naming and recognition of faces of famous people [9,10]. Some of the verbal subtests of the Wechsler Adult Intelligence Scale tap semantic memory and a more severe impairment on category than on phonological/lexical fluency tasks [11,12] may indicate impairment related to semantic memory.…”
Section: Introductionmentioning
confidence: 99%